ВЫРАЖЕНИЕ ТЕМПОРАЛЬНОСТИ В НЕМЕЦКОМ И КАРАКАЛПАКСКОМ ЯЗЫКАХ - Байниязова, С.Т. (SCIENCE and SOCIETY, 2022)
This article discusses the comparative study of the expression of the meaning of temporality in German and Karakalpak languages, as well as the opinion of well - noun linguists on the comparative study of the expression of the meaning of temporality.The author compares the expression of temporality in German and Karakalpak languages and gives examples.